Conviction : the making and unmaking of the violent brain - Rollins, Oliver (Stanford University Press, 2021)
"Neurocriminology's focus on the brain and reliance on cutting-edge technologies have helped to rewrite its history as a science used to support eugenics, racism, and genocide, and reclaim the program's credibility. However, as Oliver Rollins carefully elucidates, many questions remain about how this new rendition of an old scientific tradition will address accusations of bias and discrimination that have surrounded it since its inception. Rollins argues that because controversy has always been part of its story it is now being leveraged by scientists to justify new developments, and thus continued use of, the research"--